The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1093/embo-reports/kve097
|View full text |Cite
|
Sign up to set email alerts
|

Ecological fitness, genomic islands and bacterial pathogenicity

Abstract: The compositions of bacterial genomes can be changed rapidly and dramatically through a variety of processes including horizontal gene transfer. This form of change is key to bacterial evolution, as it leads to ‘evolution in quantum leaps’. Horizontal gene transfer entails the incorporation of genetic elements transferred from another organism—perhaps in an earlier generation—directly into the genome, where they form ‘genomic islands’, i.e. blocks of DNA with signatures of mobile genetic elements. Genomic isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
424
0
15

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 534 publications
(443 citation statements)
references
References 41 publications
4
424
0
15
Order By: Relevance
“…Shi and Falkowski 2008), which putatively plays an important role in rapidly changing environments (Rodriguez-Valera et al 2009) and niche partitioning among close relatives (Kopac et al 2014). The shell genome genes do not seem to be randomly dispersed over the chromosome, but rather concentrated within genomic islands with frequent HGT and HR events (Hacker and Carniel 2001;RodriguezValera et al 2009). However, Narechania et al (2012) showed that many core genes have an identical phylogenetic signal as shell genes, which denotes their common evolutionary history.…”
Section: Speciation Factors In (Cyano)bacteriamentioning
confidence: 99%
“…Shi and Falkowski 2008), which putatively plays an important role in rapidly changing environments (Rodriguez-Valera et al 2009) and niche partitioning among close relatives (Kopac et al 2014). The shell genome genes do not seem to be randomly dispersed over the chromosome, but rather concentrated within genomic islands with frequent HGT and HR events (Hacker and Carniel 2001;RodriguezValera et al 2009). However, Narechania et al (2012) showed that many core genes have an identical phylogenetic signal as shell genes, which denotes their common evolutionary history.…”
Section: Speciation Factors In (Cyano)bacteriamentioning
confidence: 99%
“…Следует подчеркнуть, что во всех случаях речь идет о геномах конкретных штаммов, а не о видовых геномах, поскольку внутривидовые различия в размерах геномов, в составе и количес-тве генов могут быть значительными [12]. Эти раз-личия обусловлены прежде всего вариабельностью той части генома, которую составляют гены вспомо-гательного (auxiliary [12,48]) или так называемого гибкого (flexible [35]) набора. Более консервативный базовый (core) набор, состоящий из генов «домаш-него хозяйства», обслуживает жизненно-необходи-мые информационные процессы репликации, транс-крипции, трансляции, ключевые пути метаболизма и формирования клеточных структур, определяющих видовую/родовую принадлежность организма.…”
Section: понятие о видовом геномеunclassified
“…Таким образом, интегроны играют роль своеобразных «ловушек», обеспечива-ющих функционирование захваченных кассет, содер-жащих сцепленные гены, контролирующие резистен-тность к лекарственным препаратам, патогенность, синтез ферментов катаболизма и т. п. Особенности структурной организации интегронов и более слож-ных суперинтегронов, рекомбинационные механизмы сборки и перемещения различных интегронов деталь-но рассматриваются в обзорах [2,67]. в геномных островках (ГО) совмещаются раз-личные мобильные элементы и большое число генов, обеспечивающих многокомпонентные процессы, определяющие ключевые черты образа жизни орга-низма хозяина [22,34,35]. Собранные в ГО гены, ответственные за патогенность [22,34,68], биоде-градацию ксенобиотиков [72], симбиогенез [35,63], транспорт металлов и т. д.…”
Section: плазмиды и бактериофаги [4 15 26 70]unclassified
See 2 more Smart Citations